Media Richness and Continuance Intention to Online Learning Platforms: The Mediating Role of Social Presence and the Moderating Role of Need for Cognition - Wang, Zhen (Frontiers in Psychology, 2022)
Continuance intention to online learning platforms has received increased attention in recent years, and media richness has been found to be an important antecedent influencing user retention. However, there is insufficient research on the mediating and moderating mechanism underlying this relation. The purpose of this paper is to investigate (a) the positive association between three dimensions of media richness and user continuance intention, (b) the mediating role of social presence in the relation between three dimensions of media richness and continuance intention, and (c) the moderating role of need for cognition in the relation between three dimensions of media richness and social presence. We conduct a survey questionnaire with a sample of 368 users from online learning platforms and use structural equation modeling. The results indicate that the model proposed has a high explanatory power of continuance intention to online learning platforms and give support to the moderating role of need for cognition (NFC). The study highlights the crucial role these technological-environment-related variables (media richness) have in relation to virtual user experience (social presence) and their continuance intention. Furthermore, this study shows the significance of differentiated online course design to foster users’ social presence according to user types.